2009
DOI: 10.1002/jmor.10766
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal development in the Chinese soft‐shelled turtle Pelodiscus sinensis (Testudines: Trionychidae)

Abstract: We investigated the development of the whole skeleton of the soft-shelled turtle Pelodiscus sinensis, with particular emphasis on the pattern and sequence of ossification. Ossification starts at late Tokita-Kuratani stage (TK) 18 with the maxilla, followed by the dentary and prefrontal. The quadrate is the first endoskeletal ossification and appears at TK stage 22. All adult skull elements have started ossification by TK stage 25. Plastral bones are the first postcranial bones to ossify, whereas the nuchal is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 55 publications
(80 reference statements)
3
92
0
Order By: Relevance
“…Turtle skeleton formation has been studied in multiple species from hardshelled to soft-shelled turtles and from side-necked (Pleurodira) to hidden-neck turtles (Cryptodira) (33,(36)(37)(38)(39)(40). These studies have emphasized the development of the carapacial skeleton, following the order of mineralization of skeletal elements during late embryogenesis and comparing carapace development between different species of turtles.…”
Section: Resultsmentioning
confidence: 99%
“…Turtle skeleton formation has been studied in multiple species from hardshelled to soft-shelled turtles and from side-necked (Pleurodira) to hidden-neck turtles (Cryptodira) (33,(36)(37)(38)(39)(40). These studies have emphasized the development of the carapacial skeleton, following the order of mineralization of skeletal elements during late embryogenesis and comparing carapace development between different species of turtles.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies have interpreted heterochrony only when events are reported using both optimization approaches, we have previously shown that Parsimov is overly conservative, and using either ACCTRAN or DELTRAN (not both) may be justified in some cases [19]. Furthermore, following Hautier et al [19] and Sánchez-Villagra et al [29], we performed additional Parsimov analyses with all ties converted to missing data (electronic supplementary material, S3 and S4) to control for the artefactual interpretation of heterochrony owing to accumulation of ties across events. We did not use the Pgi heterochrony search algorithm by Harrison & Larsson [30], as it is currently not programmed to analyse datasets with ties excluded [19].…”
Section: (A) Data Collectionmentioning
confidence: 99%
“…As in other amniotes, the turtle shoulder girdle maintains its position relative to the muscle plate throughout development via a unique muscle folding mechanism, in some cases maintaining ancestral connectivities and in others creating novel ones [15]. However, the entire pectoral girdle remains anterior to the cartilaginous first dorsal rib throughout ontogeny, and only becomes encapsulated within the shell upon intramembranous ossification of the nuchal bone, the dorsal ribs and neural spines of the carapace [18]. Indeed, as has long been noted by skilled anatomists [19], the scapula remains anterior to the first dorsal rib even in adult turtles.…”
Section: Introductionmentioning
confidence: 99%